THE ROLE OF TECHNOLOGY IN THE GROWTH OF THE GIG ECONOMY PERTAINING TO ONLINE TUTORING SERIVES - Saravanan, A.; Arockiamary, R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Recent technological developments that allow for flexible, on-demand work have played a major role in the gig economy’s notable expansion. Online tutoring services are a significant industry in our economy, and their growth is largely attributable to digital platforms that enable distant, real-time learning. This study examines how technology has contributed to the growth of online tutoring, emphasizing important elements like usability, scalability, and accessibility. Tutoring platforms are now able to efficiently match instructors with students, personalize learning experiences, and provide smooth interactions across international locations thanks to the integration of advanced algorithms, cloud computing, and virtual communication technologies. The technological foundations of the online tutoring industry are highlighted in this paper, along with its role in the gig economy and prospects for expansion and innovation.